Biological implications and clinical value of mir-210 in gastrointestinal cancer. (3rd June 2017) - Yang, Wanli; Ma, Jiaojiao; Zhou, Wei; Zhou, Xin; Cao, Bo; Fan, Daiming; Hong, Liu
ABSTRACT: Introduction: Hypoxia, a common feature of tumor microenvironment, is known to accelerate tumor development and growth by promoting the formation of a neoplastic environment. Recent studies have provided a wealth of evidence that miRNAs are significant members of the adaptive response to low oxygen in tumors. miR-210 is one of the hypoxia-induced miRNAs, which has been reported extensively in cancer researches. However, there is no systematic discussion about the role of miR-210 in gastrointestinal cancer. We conducted a literature research in database including PubMed, Elsevier Science Direct and Medline before 16 September 2016, in order to collect articles of miR-210 in gastrointestinal cancer. Areas covered: In the present review, we mainly discuss the following aspects: hypoxia-induced dysregulation of miR-210, the expression of miR-210 and tumorigenesis, the resultant changes of miR-210 targets and its roles in different types of gastrointestinal cancer progression, the diagnostic, therapeutic and prognostic value of miR-210 in gastrointestinal cancer. Expert commentary: Numerous researches have demonstrated the values of miR-210 in cancer diagnosis, prognosis and targeted therapies, especially in gastrointestinal cancers. However, there are also some existing problems and challenges in translating the new research findings into clinical utility. Further investigations and studies are still urgently required.